Determining the success factors of settlements based on the experience of village- research - Molnár Nagyné, Melinda (Studia Mundi – Economica, 2020)
The settlements are value-carriers. Of course not every valuable condition is a key of the success. The objective of this study is to survey the general success factors of settlements. The settlements as autonomies due to their far-reaching role-system possess means of different characteristics, which can strengthen or even weaken each other’s effects. One part of the instruments used by the settlements are unique, whereas other instrument work alike everywhere. The success of settlement depends on whether they are aware of the factors that determine their success, and whether they find their own effective tools to reach their objectives. This study presents which factors could we identify that determine success, based on our village seminar researches that have been ongoing since 2007.